Effective health care for older people living and dying in care homes: a realist review - Goodman, Claire; Dening, Tom; Gordon, Adam L.; Davies, Susan L.; Meyer, Julienne; Martin, Finbarr C.; Gladman, John R.F.; Bowman, Clive; Victor, Christina; Handley, Melanie; Gage, Heather; Iliffe, Steve; et al. (BIOMED Central, 2016)
Background: Care home residents in England have variable access to health care services. There is currently no coherent policy or consensus about the best arrangements to meet these needs. The purpose of this review was to explore the evidence for how different service delivery models for care home residents support and/or improve wellbeing and health-related outcomes in older people living and dying in care homes. Methods: We conceptualised models of health care provision to care homes as complex interventions. We used a realist review approach to develop a preliminary understanding of what supported good health care provision to care homes. We completed a scoping of the literature and interviewed National Health Service and Local Authority commissioners, providers of services to care homes, representatives from the Regulator, care home managers, residents and their families. We used these data to develop theoretical propositions to be tested in the literature to explain why an intervention may be effective in some situations and not others. We searched electronic databases and related grey literature. Finally the findings were reviewed with an external advisory group. Results: Strategies that support and sustain relational working between care home staff and visiting health care professionals explained the observed differences in how health care interventions were accepted and embedded into care home practice. Actions that encouraged visiting health care professionals and care home staff jointly to identify, plan and implement care home appropriate protocols for care, when supported by ongoing facilitation from visiting clinicians, were important. Contextual factors such as financial incentives or sanctions, agreed protocols, clinical expertise and structured approaches to assessment and care planning could support relational working to occur, but of themselves appeared insufficient to achieve change.